New and Noteworthy in Nutrition - Gillespie, Stuart (International Food Policy Research Institute, 2003)
True to form, governments have reacted with all the strategic competence of rabbits caught in headlights." Ex-Boomtown Rat, current debt relief campaigner, Sir Bob Geldof, on the situation in Africa, 17 years after the 'Live Aid' concerts were first held in response to famine in Africa. Noting that while under the Heavily Indebted Poor Countries (HIPC) Initiative some 26 countries are now getting debt relief, half of them still pay more than 15 percent of government revenue to creditors, Geldof is calling for a total cancellation of debt. More than 38 million people across Africa are currently at risk of starvation, according to WFP. Hardest hit are the Horn of Africa, where about 17.9 million people face severe food shortages, and southern Africa, where 16.4 million are at risk, the agency said.